Univariate characterization of the German business cycle 1955-1994 - Claus Weihs; Ursula Garczarek (Universität Dortmund, Sonderforschungsbereich 475 - Komplexitätsreduktion in Multivariaten Datenstrukturen, 2002)
We present a descriptive analysis of stylized facts for the German business cycle. We demonstrate that simple ad-hoc instructions for identifying univariate rules characterizing the German business cycle 1955-1994 lead to an error rate comparable to standard multivariate methods.
Keywords: 519; descriptive analysis; parallel box plots; multivariate classification; univariate rules; business cycle; Konjunktur; Zeitreihenanalyse; Deskriptive Statistik; Deutschland